The Power to Tax in Europe - Lindholm, Johan; Hultqvist, Anders (Swedish Studies in European Law, 2023)
This open access book is the seventeenth volume in the Swedish Studies in European Law, reflecting the series aim to explore the variety of issues and dilemmas that European law faces in specific areas of EU law and policy, as well as overarching questions of EU institutional and constitutional law. In this volume, experts explore the development of the role of Europe and European law in the field of taxation. The eBook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com. Open access was funded by Swedish Studies Network.